Recovery of mercury from dental amalgam scrap-Indian perspective - Kadandale Sadasiva; Sreeram Rayar; Unnikrishnan Manu; Kumarappan Senthilkumar; Srinivasan Daya; Nagarajan Anushaa (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim is to recycle mercury from dental amalgam scrap using the vacuum distillation method. Materials and Methods: A total of 150 g of dental amalgam scrap was taken in a round bottom flask and was subjected to vacuum distillation at 398°C. The vapor of mercury was collected in another round bottom flask. Observation: The procedure is carried out for mercury recovery using vacuum distillation apparatus, and mercury vapor are collected in a round bottom flask, and the silver is recovered using sucrose as reducing agent. Using 150 g of dental amalgam scrap 50%-80% of silver are recovered, and silver has a purity of 70%-80%. However, the total time required in the reduction process ranged between 303 and 600 min. Conclusion: Mercury could be recycled from dental amalgam scrap through vacuum distillation method at 398°C and its implication of dental amalgam scrap in an Indian perspective.